Upaya Meningkatkan Hasil Belajar Matematika Tentang Operasi Hitung Pecahan pada Peserta Didik Kelas VI A SD Negeri Kasreman melalui Metode Teams Games Tournament (TGT) di Semester II Tahun Pelajaran 2018/2019 - Rokhimah, Rokhimah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The purpose of this research is to analyze the mathematic learning outcome about the Calculation of the Fraction of the students of Class VI A the Elementary School of Kasreman with the Teams Games Tournament (TGT)Method on the Second Semester of the 2018/2019 year academic. The type of this research is a Class Action Research (CAR). The place of this research is Class VI A the Elementary School of Kasreman, Sub District of Kasreman, Regency of Kasreman. The time of this research is the early period on the Second Semester of the 2018/2019 year academic. The subjects of this research are as much as twenty one children; consist of fourteen boys and seven girls. Techniques of collecting data of this research are using non test technique and test technique. Technique of analyzing data of this research is using comparative description. The results of this research are 1) the mathematic learning about the Calculation of the Fraction with the Teams Games Tournament (TGT)Method is a small group with heterogenic composition, 2) the mathematic learning about the Calculation of the Fraction with the Teams Games Tournament (TGT)Method is performing the task with the team and tournament with the delegation system, 3) the mathematic learning about the Calculation of the Fraction with the Teams Games Tournament (TGT)Method is a continuing section tournament and also direct collective one, 4) the mathematic learning about the Calculation of the Fraction with the Teams Games Tournament (TGT)Method is improving the students’ the learning activities: active (B) in discussing with the team, active (B) in answering the questions form the teacher and other students and active(B)    in asking the questions to the teacher, 5) the mathematic learning outcome about the Calculation of the Fraction with the Teams Games Tournament (TGT)Method is improving, from not good category into good one. The learning outcome on the Early Condition is 54,76 for the average and 23,81% for the completeness. The learning outcome on the First Cycle is 70,95 for the average and 66,66% for the completeness. The learning outcome on the Second Cycle is 80,47 for the average and 85,71% for the completeness.